Measuring Importance, Performance, and Frequency of Green Initiatives among North Carolina Bed and Breakfast Operators: A Pilot Study - Sanderson, Mary S. (East Carolina University, 2013)
A bed and breakfast (B&B) is a house or small hotel where someone can rent a room for a price that includes breakfast the next morning (Bed and Breakfast, 2012). According to Tsai (2008), green hotels are lodging facilities that use "operation techniques that have a low impact on the environment, while maintaining their business environment, to provide clients with green products (meals), green services (housekeeping), and living environments that are natural, healthy, clean, and comfortable" (p.286). In order to better understand the adoption of green practices within the NC B&B industry, the purpose of this study was to investigate, not only how important green initiatives are to owner/operators, but also how frequently they are performed. The research design that this study employed was a cross-sectional design, and an importance-performance analysis (IPA) was used to analyze the data. From the data gathered for this study, a list of most frequently used green practices of North Carolina B&Bs was generated. The results of the study showed that NC B&Bs are implementing green practices well in all categories, except for marketing.
Keywords: Bed and breakfast (B&B); North Carolina; Importance-performance analysis (IPA); Green initiatives; Pilot study; Sustainability